Synthesis and Characterizations of DOPO Substituted Polyesters - Sefa, Damla Cansu; Ozmen, Fadime Karaer; Ureyen, Mustafa E.; Eren, Tarik (WILEY-V C H VERLAG GMBH, 2025)
Growing environmental and health concerns regarding the use of halogenated flame retardants have led to an increased interest in phosphorus-based alternatives, which are recognized for their environmentally friendly properties. In this study, phosphorus-functional monomers, obtained via phospho-Michael addition of DOPO to unsaturated compounds such as maleic anhydride and itaconic acid, were incorporated into polyester matrices to impart intrinsic flame retardancy through covalent integration into the polymeric network. The influence of terephthalic acid on the thermal behavior of these polyesters is also explored. A range of analytical techniques are employed to inform the study, including 1H and 31P NMR spectroscopy, FTIR, viscosity evaluation, and inductively coupled plasma optical emission spectrometry (ICP-OES). Thermogravimetric analysis in combination with evolved gas analysis is used to assess thermal stability in both nitrogen and air environments. Furthermore, microscale combustion calorimetry is employed to examine flammability characteristics. For cone calorimetry tests, polyester samples are applied onto glass fibers to evaluate their flame-retardant efficacy, smoke generation, and overall fire safety performance.
Keywords: Bio-based polymer; DOPO; Halogen-free flame retardant; Phosphorus flame retardant; Polyesters; FLAME-RETARDANT; COPOLYESTERS; Chemistry